Liposomal formulation of Galbanic acid improved therapeutic efficacy of pegylated liposomal Doxorubicin in mouse colon carcinoma - Nik, Maryam Ebrahimi (Sci Rep, 2019)
Galbanic acid (Gba), a sesquiterpene coumarin, with strong antiangiogenic activity could serve as an excellent anti-cancer agent. However, Gba is a poor water-solube which hampered its clinical application. In this study, a pegylated liposomal Gba (PLGba) with HSPC/Cholesterol/mPEG(2000)-DSPE (56.2, 38.3, 5.3% molar ratio) was developed by the thin film hydration plus extrusion and calcium acetate gradient remote loading method, to address the issue of poor Gba solubility. Moreover, an integrin-targeting ligand (RGD peptide, cyclo[Arg-Gly-Asp-D-Tyr-Cys]) was post-inserted into liposomes in order to increase Gba cell delivery. Using fluorescently-labeled model liposomes, it was found that the targeting could improve the integrin-mediated cellular uptake of the liposomes in vitro in human umbilical vein endothelial cells (HUVECs), and in vivo as evidenced by chicken chorioallantoic membrane angiogenesis (CAM) model. It also could enrich the liposome accumulation in C26 tumor. Interestingly, co-treatment with PLGba and pegylated liposomal doxorubicin (PLD, also known as Doxil(®)) had a synergistic and antagonistic antiproliferative effect on the C26 tumor cell line and the normal HUVEC, respectively. In C26 tumor bearing BALB/c mice, the PLGba and PLD combinatorial therapy improved the antitumor efficacy of the treatment as compared to those of single agents. This results have clear implications for cancer therapy.